Persepsi Siswa Terhadap Model Pembelajaran Blanded Learning Dengan Motivasi Belajar Siswa di SMA Xaverius Ambon - L.M. Sahetapy; Maria S. Sabubun; L.J. Lokollo (Peneliti.net, 2022)
The purpose of this study was to determine students' perceptions of the Blended Learning Learning Model with the Learning Motivation of Xaverius Ambon High School students. The type of research used in this research is Qualitative Research. The conclusion in this study is that there are student perceptions of the blended learning model with student learning motivation. These results can be seen in data analysis and hypothesis testing with product moment correlation, the value of rcount > rtable is 0.469 > 0.374 at a significance level of 5%. Because rcount > rtable, H0 is rejected, which means there is a perception of the blended learning model with student learning motivation at Xaverius Ambon High School, and it can be seen from the results of the coefficient of determination which shows a value of 21.99% the contribution of variable X to Y